Social Media Marketing Strategy for Asian Belly Food in Forming Brand Awarendess - Gitta Pramesti, Tiara; Purnamasari, Oktaviana (PT Literasi Nusantara Publisher, 2023)
Social Media Marketing is a strategy that many business people choose to carry out promotional activities on social media. Especially with the many business users who have chosen social media as their platform of choice. This study aims to determine the Social Media Marketing Strategy implemented by Asian Belly Food in Forming Brand Awareness. The theory used in this study is the Social Media Marketing theory according to Quesenberry using a qualitative approach. as well as a descriptive method. The data collection technique used was an in-depth interview method with Product Manager and Head Creative Marketing informants as well as documentation on Asian Belly Food. The results of this study Asian Belly Food have gone through five stages of the appropriate Social Media Marketing Strategy according to Quesenberry. As a result of the implementation of the five stages, Asian Belly Food was able to create awareness, but there were still two stages that were not maximized and could be optimized.